A Holistic Quality Evaluation, Selection and Improvement Approach driven by Multilevel Goals and Strategies - Rivera, María Belén (2016)
Organizations should establish business goals and check for their achievement in a systematic and disciplined way. In order to know if a business goal is achieved, it should be necessary to consider information need goals that also can require satisfying measurement and evaluation goals at operational level. Furthermore, if measurement and evaluation goals are not aligned with top-level business goals such as tactical or strategic level goals, the organization could waste its effort and resources. Usually, the different goals established in an organization are operationalized through projects. For a given project, strategies should be used in order to help in the goal achievement. A strategy defines a set of activities and methods to be followed for a specific goal purpose. Ultimately, to engineering all these issues in a systematic way, organizations should adopt a holistic evaluation approach supported by a set of integrated strategies. By means of a systematic literature review as research method, we have observed that very few approaches support integrated strategies and multilevel goals. To bridge this gap, we have developed a holistic quality multilevel and multipurpose evaluation approach that ties together multilevel goals, projects and integrated strategies. As contributions, this paper discusses an enhanced conceptual base (specified by ontologies) for linking business and information need goal concepts with project, strategy and nonfunctional requirements concepts. Then, it defines the step by step of our holistic quality evaluation approach, by listing the necessary activities to establish goals and projects at different organizational levels. Lastly, it specifies and illustrates evaluation scenarios for business/information need goal purposes such as understanding, improving, monitoring and controlling, comparing and selecting entities, which are supported by strategies and strategy patterns.